Maintaining Consistency in Managing Campaign Through Websites at KapanLagi Youniverse - Yohanes Stephen Gracia Djohan; Nila Pusvikasari; Agustinus Sri Wahyudi; Erika Jimena Arilyn (Jurnal Abdimas Sosial, Ekonomi, dan Teknologi, 2022)
This internship report is intended to explain the author's activities in the internship process with KLY (Emtek Digital) through the MBKM program organized by the Ministry of Education and Culture. This program aims to provide opportunities for college students to experiencing work professionally in a company, understanding the company's work culture, gaining various knowledge and skills needed in the world of work. This internship report contains the author's activities as part of the Campaign Manager Intern including the tasks within the Campaign Management division and some of the main tasks that was trusted by the mentor for author to do. As for this report, it will explain author's activities as a Campaign Manager for Kapanlagi Youniverse in collaboration with several teams from other divisions. The MBKM program trains author to be able to implemented the skills that have learned such as effective communication, project management, and analytical thinking into work related to managing campaigns.